RESPONS CEKAMAN GARAM TERHADAP PERTUMBUHAN DAN KONSENTRASI RANTAI PANJANG POLYISOPRENOID PADA MANGROVE Sonneratia alba Smith. - Latifah Nur Siregar; Mohammad Basyuni; Lollie AP Putri (Peronema Forestry Science Journal, 2015)
Mangrove is one of the richest bioactive source naturally and is able to remove excess of salt. The purpose of this study was to determine optimum salinity concentration for growth of S. alba seedlings and to evaluate effect of salinity on polyisoprenoid composition. S. alba seedlings were used  with 5 treatments namely 0%, 0,5%, 1,5%, 2%, and 3%  grown for 3 months. Results showed that optimum growth for S. alba seedlings characterized by height, diameter, and dry weight of root in 1,5% salinity, the best number of leaves and moisture content of root were  in 0,5% salinity. On the other hand,  dry weight of shoot, moisture content of shoot, and ratio of shoot to root were found in 3% salinity, respectively. Analysis of Polyisoprenoid in S. alba seedlings in 3% salinity was higher concentration than 0% treatment. Key words : mangrove, Sonneratia alba, salinity, polyisoprenoid